REALITY SHOW BIG BROTHER DALAM PERSPEKTIF GENRE DAN OTHER CLASSIFICATIONS - M. Haqqi Anna Zilli (Institut Agama Islam Negeri Bengkulu, 2017)
Reality show is a television program that presents real events in everyday life. With the number of reality shows that appear on TV favored by the public, for example Uya is Kuya, still another world, termehek-mehek, So the more loss of ideas and justify any means to attach importance to the rating. Reality show displays a fake reality to dredge advertising alias profit. The reality show that appears on TV is not only concerned with rating, but also can incorporate moral values. The reality show program, “Big Brother” shows the daily activities of the participants and of course uses surveillance cameras. Big Brother is included in a reality show that is full of engineering and does not fit reality because it has a storyline that has been conceptualized by TV stations. The real thing of the event is the games or games and the unreal is the story of the story of the participants. The phrases that are often pronounced in this event are the participants or the so-called housemates. Although some viewers really like the Big Brother show, but what is displayed does not match the reality that exists. Although by using fact frills, but still there are still being engineered by the event editor. We should be wise to see an event program. Do not just accept it, but we must also be critical in responding.